Indigo- and indirubin-producing strains of Proteus and Psychrobacter are associated with purple rind defect in a surface-ripened cheese. (December 2018) - Kamelamela, Noelani; Zalesne, Michael; Morimoto, Joshua; Robbat, Albert; Wolfe, Benjamin E.
Abstract: The rinds of surface-ripened cheeses have expected aesthetic properties, including distinct colors, that contribute to overall quality and consumer acceptance. Atypical rind pigments are frequently reported in small-scale cheese production, but the causes of these color defects are largely unknown. We provide a potential microbial explanation for a striking purple rind defect in a surface-ripened cheese. A cheese producer in the United States reported to us several batches of a raw-milk washed-rind cheese with a distinctly purple rind. We isolated a Proteus species from samples with purple rind defect, but not from samples with typical rind pigments, suggesting that this strain of Proteus could be causing the defect. When provided tryptophan, a precursor in the indigo and indirubin biosynthesis pathway, the isolated strain of Proteus secreted purple-red pigments. A Psychrobacter species isolated from both purple and normal rinds also secreted purple-red pigments. Using thin-layer chromatography and liquid chromatography-mass spectrometry, we confirmed that these bacteria produced indigo and indirubin from tryptophan just as closely related bacteria make these compounds in purple urine bag syndrome in medical settings. Experimental cheese communities with or without Proteus and Psychrobacter confirmed that these Proteobacteria cause purple pigmentation of cheese rinds. Reports of purple rinds in two other cheeses from Europe and the observation of pigment production by Proteus and Psychrobacter strains isolated from other cheese rinds suggest that purple rind defect has the potential to be widespread in surface-ripened cheeses. Highlights: Purple rind defect is caused by the bacteria Psychrobacter and Proteus in cheese rinds. Psychrobacter and Proteus cause rinds to turn purple through indirubin and indigo production. Indirubin and indigo production is a trait found across cheese isolates of Psychrobacter and Proteus .